Norrin in cancer: from a promising prognostic biomarker to a novel therapeutic target - Zhang, Jiaqing; Zhang, Zhengyi; Xiong, Huabao; Dong, Guanjun; Yu, Lu (Frontiers in Oncology, 2025)
Cancer continues to pose significant risks to public health globally due to incomplete therapeutic conquests even though significant advances have been achieved in the field of oncology. Therefore, understanding the molecular mechanisms driving tumorigenesis and progression is critical for developing novel treatment strategies to achieve effective cancer treatment. Norrin, the secreted cystine-knot protein originally recognized for its functional role in retinal vascular development an neuronal protection, is now implicated in oncogenic processes. This review synthesizes the existing evidence on Norrin’s involvement in tumors, highlighting its aberrant expression across multiple malignancies and its functional role in cancer cell proliferation, migration, invasion, and tumor-associated angiogenesis. The compelling data reported in this review suggest that dysregulated Norrin signaling promotes oncogenesis in various cancer types. Furthermore, the mechanistic basis of Norrin’s tumorigenic effect is discussed, and the therapeutic potential of targeting Norrin is evaluated to provide novel insights for future diagnostic and therapeutic development in oncology.